FAKTOR-FAKTOR YANG MEMENGARUHI VOLUME KREDIT YANG BERDAMPAK PADA PROSIKLIKALITAS: STUDI KASUS BANK DOMESTIK DAN ASING DI INDONESIA - Indri Arrafi Juliannisa; Kartika Pakpahan (Center for Economic Studies Universitas Katolik Parahyangan, 2017)
The volume of bank credit could lead to procyclicality problems. This study analyzes the factors that influence the volume of bank credit. This study uses panel data regression, with monthly data on credit volume, Non Perfoming Loan (NPL), Third-Party Funds (DPK) and Capital Adequacy Ratio (CAR) of domestic and foreign banks, from January 2013 until August 2014. NPL, DPK, and CAR are used as independent variables. The research result shows that Fixed Effect method is the best technique to show the significant variable which influence the volume of bank credit. In addition, NPL and CAR have significant influence on the volume of the bank credit.Keywords: NPL, DPK, CAR, Credit, Procyclicality